A prospective hospital-based study on C-reactive protein as a response predictor of antidepressant treatment in drug naïve patients with major depressive disorder - Didakamiwan Khonglah; Arghya Pal; Nitu Mallik; Debes Ray; Malay Ghosal; Rudraprasad Acharya (Indian Journal of Psychiatry)
Background: C-reactive protein (CRP) is an acute phase reactant that is implicated in the pathogenesis of major depressive disorder (MDD), due to its role in the execution of various important neurological events, including neurogenesis, mediation of neural plasticity, and synaptic transmission. Aims: This study was conducted to determine the relationship between the level of CRP to remission rates after antidepressant therapy. Methods: Fifty patients of first episode MDD with no past history of antidepressant exposure and other medical comorbidity were recruited after obtaining consent for Escitalopram therapy. The CRP levels of the patients were evaluated on the day of recruitment and depressive symptoms were monitored using Montgomery–Asberg Depression Rating Scale at weeks 0, 3, 6, and 12. The patients with low (≤10 mg/l) and high (>10 mg/l) CRP levels were compared for time taken to achieve remission using Kaplan–Meier survival analysis. Results: The Kaplan–Meier survival analysis showed a significantly higher proportion of patients with low CRP levels attained remission than patients with higher CRP levels (Log-rank = 7.594; dF = 1; P = 0.006). The age, compliance to pharmacotherapy, and disability did not significantly affect the remission rates of the patients. Conclusion: Our study confirms that higher levels of CRP can lead to poorer remission rates in patients with MDD after antidepressant therapy and can predict treatment resistance.